Maternal periconception food insecurity and postpartum parenting stress and bonding outcomes - Shreffler, Karina M.; Dressler, Caitlin M.; Ciciolla, Lucia; Wetherill, Marianna S.; Croff, Julie M. (Frontiers in Nutrition, 2024)
Food insecurity during pregnancy is associated with various adverse pregnancy outcomes for the mother and infant, but less is known about the role of periconception food insecurity and its links to maternal and child wellbeing in the postpartum period. In a sample of 115 diverse (41% white) and predominately low-income mothers, results of hierarchical regression analyses showed that periconception food insecurity was positively associated with parenting stress at two months postpartum. A negative association between food insecurity and maternal-infant bonding at six months postpartum was mediated after controlling for prenatal depression, social support, and demographic factors. Findings highlight the need for maternal linkage to effective food security programs, such as United States-based Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), for women during their childbearing years due to the critical importance of food security for maternal and infant well-being.